BASED ANALYSIS OF INTERACTION BETWEEN HUMAN SUBJECT AND ARTIFICIAL SYSTEM - IMPACTS OF DRIVER ATTENTION FAILURES ON TRANSPORT RELIABILITY AND SAFETY (Perner's Contacts, 2011)
The interaction between human subject and artificial, namely technical equipment represents one of the most important factors influencing the operation reliability and safety of almost all existing systems with which the human society has to deal. The need to minimize these losses is the dominant motivation for activity in this area. Let us restrict here to the car-driver and vehicle interaction.